137k views
1 vote
Solve for the variable: -(3x)^2 + 3 = -6

User Aytek
by
6.3k points

2 Answers

5 votes
Done there you go your answer
Solve for the variable: -(3x)^2 + 3 = -6-example-1
User Charleso
by
5.9k points
6 votes

Hey there! :)


-(3x)² + 3 = -6


Simplify.


-(9x²) + 3 = -6


Simplify.


-9x² + 3 = -6


Subtract 3 from both sides.


-9x² = -6 - 3


Simplify.


-9x² = -9


Divide -9 from both sides.


-9x² ÷ -9 = -9 ÷ -9


Simplify.


x² = 1


So, x = 1 OR x = -1


~Hope I helped!~

User Wayneh
by
6.2k points